Cutting the Gordian Knot: Or How to Preserve Non-Current Clinical Records Without Being Buried in Paper - Maxwell-Stewart, Hamish; Tough, Alister (Archivaria, 1996)
The quantity of hospital clinical records generated in the last fifty years is widely perceived as a problem, not least because of the storage accommodation required to house hard copy records and the costs involved in converting them to less bulky media. The authors of this paper argue that the real problem is not bulk but lack of use. This in turn is the consequence of inadequate indexing and contextual information structures. At present access to non-current clinical records is difficult and inherently haphazard. As a result, the constituency of actual users is small. Yet potentially valuable data, particularly for epidemiologists and clinical researchers, is contained within these records. In the course of research conducted in the British National Health Service (NHS) a variety of possible solutions to both the perceived and real problems have been examined. The recommendations made, although addressed primarily to the circumstances of the NHS in Scotland, may be relevant elsewhere. The scheme advocated here is intended to create a "virtuous circle" of use leading to a willingness to regard clinical records as a resource to be utilized and valued rather than as a problem. Some of the issues and alternatives considered in respect of clinical records are relevant to the appraisal of other series of PIPs (Particular Instance Papers): they also have implications for the collection and storage of data in electronic form. RÉSUMÉ La masse des dossiers cliniques des hôpitaux générés durant les cinquante dernières années est largement perçue comme un problème, tant au niveau de l’espace requis pour leur entreposage que des coûts afférents à leur conversion sur des supports moins volumineux. Les auteurs du présent article soutiennent que le problème réel n’en est pas un de volume mais plutôt d’inutilisation; laquelle résulte d’un classement inadéquat ainsi que d’une information contextuelle lacunaire. Présentement, l’accès aux dossiers cliniques non actifs est ardu et se fait plutôt à l’aveuglette. Ainsi le nombre réel d’utilisateurs de ces dossiers est peu élevé malgré la grande valeur potentielle de ces informations, spécialement pour les épidémiologistes et les cliniciens. Durant le cours de la recherche menée au British National Health Service un éventail de solutions possibles aux problèmes, aussi bien présumés que réels, a été examiné. Les recommandations, bien que conçues pour le National Health Service d’Écosse, peuvent aussi s’avérer pertinentes dans d’autres milieux. Le plan défendu ici a pour but de créer une «tangente» visant à envisager les dossiers cliniques comme une ressource utilisable et valable plutôt qu’uniquement comme une source d’embarras. Quelques unes des questions et alternatives soulevées ici à propos des dossiers cliniques sont également pertinentes pour l’évaluation de d’autres séries du PIPS (Particular Instance Papers); elles ont également des incidences sur la collecte et la conservation des données informatisées.